2021
DOI: 10.1002/casp.2563
|View full text |Cite
|
Sign up to set email alerts
|

Community resilience and anxiety among Chinese older adults during COVID‐19: The moderating role of trust in local government

Abstract: The worldwide spread of COVID‐19 has resulted in an enormous threat to public health, causing global panic, especially older adults suffering severe anxiety due to their vulnerability. With a questionnaire survey on 213 Chinese older adults in April 2020, we examined the role of community resilience in protecting older adults from anxiety during the COVID‐19 pandemic, and simultaneously considered the moderating role of trust in local government. The results indicated that community resilience was negatively a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 42 publications
(58 reference statements)
0
16
0
Order By: Relevance
“…Furthermore, our findings point towards the central role of trust during crises, showing that experiences of distrust of others, one’s community or neighbours, and of the UK governments’ handling of the pandemic led to social tensions and polarisation at every level. Similarly, trust in government was found to mediate the association between community resilience and anxiety during the COVID-19 pandemic ( Zhang et al , 2021 ) and to be associated with greater compliance with COVID-19 measures ( Dohle et al , 2020 ). Recent research on the role of social cohesion in the UK further suggests that investments in community integration programmes prior to the pandemic helped individuals and communities cope better with the impacts of COVID-19, and resulted in stronger and more connected communities, as measured by higher levels of reported social activism, closer personal relationships, and greater interpersonal and political trust ( Lalot et al , 2021 ).…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, our findings point towards the central role of trust during crises, showing that experiences of distrust of others, one’s community or neighbours, and of the UK governments’ handling of the pandemic led to social tensions and polarisation at every level. Similarly, trust in government was found to mediate the association between community resilience and anxiety during the COVID-19 pandemic ( Zhang et al , 2021 ) and to be associated with greater compliance with COVID-19 measures ( Dohle et al , 2020 ). Recent research on the role of social cohesion in the UK further suggests that investments in community integration programmes prior to the pandemic helped individuals and communities cope better with the impacts of COVID-19, and resulted in stronger and more connected communities, as measured by higher levels of reported social activism, closer personal relationships, and greater interpersonal and political trust ( Lalot et al , 2021 ).…”
Section: Discussionmentioning
confidence: 96%
“…The copyright holder for this preprint this version posted February 10, 2023. ; https://doi.org/10.1101/2023.02.07.23285620 doi: medRxiv preprint population but also in COVID-19 patients (Moret Tatay & Murphy, 2022;Song et al, 2021;Zhang et al, 2020Zhang et al, , 2022. Thus, higher levels of resilience among patients with post-COVID-19 syndrome can reduce negative consequences, protect patients against adverse events, and promote patients' ability to cope with this condition.…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%
“…In other words, when individuals perceive that the measures made by the local government are strongly effective in preventing and stopping the spread of COVID-19, they may view the local government as credible and trustworthy ( 52 ). Existing studies have indicated that individuals' trust in the local government can decrease their perceptions of risk related to the COVID-19 crisis ( 53 ). Shanka and Menebo ( 18 ) also found that individuals' trust in the government is a strong predictor of their behaviors, and those who have more trust in local government are less likely to complain about the policies and measures, and more likely to be confident in dealing with COVID-19.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%